Blended Learning in a Reading Course: Undergraduate EFL Students’ Perceptions and Experiences - NOVA LINGGA PITALOKA; HESTI WAHYUNI ANGGRAINI; DEDI KURNIAWAN; ERLINA ERLINA; HARISWAN PUTRA JAYA (Universitas Jambi, Indonesia, 2020)
Research on blended learning in reading course especially is limited. This study aimed at revealing the implementation of blended learning in reading course for undergraduate EFL students at one public university in South Sumatera and the students’ perceptions on the e-learning incorporated in the blended learning in the reading course. The study was carried out through a qualitative method using a case study approach. The first semester students, consisting of 13 female and 5 male students, majoring in English Education Study Program at a public university in South Sumatera participated in this study. The researchers used observations, documents, and semi-structured interviews to collect the data. The collected data were analyzed qualitatively. The findings covered two major issues in accordance with the research questions: the implementation of the blended learning and students’ perceptions of the e-learning. The findings showed that in the reading course, 4 meetings were conducted with e-learning and 12 others were employed in the classroom with various activities. In terms of students’ perceptions, the students reported some advantages and challenges that they encountered in e-learning. This study also provided some implications and recommendations for further research.